Newspaper Language in Representing Ethnic Violence: Textual Analysis of Kompas dan Republika Newspapers - ., Prayudi (Jurnal ILMU KOMUNIKASI, 2004)
The reconceptualization of ethnicity came to its peak when the New Order regime introduced the policy of ‘suku’ (ethnic), ‘agama’ (religion), ‘ras’ (racial) or ‘antar golongan’ (inter-group). The policy, known as SARA, was meant to limit and control public interpretation over all socio-political conflicts that may endanger national stability and to restrict languages used in the news media. The policy had became the main foundation of all government policies related to society. Conflicts should be avoided and difference within society was intolerable. The Indonesian press then faced a dilemma when it came to reporting issues of ethnicity. On one side, they had an obligation to report the news to public; on the other side, the concept of SARA had become an unwritten law to restrict the press from reporting the issue. Further, the government could revoke the publishing permits without any warning it thought that the press had broken the law. The objective of the research was to define and analyze the usage of language in national newspapers in representing ethnicity issues. The analysis focused on the 1997 ethnic violence in West Kalimantan.